(3ebGdI aj GSJYeGd MLQ GdHGORgQ GdMjhGfis - (3GdbhUhfj , TeS GdOjf eMeO Hf eMeO Hf eMeO Hf HOQ GdOjf GdbhUhfj,J (B931 (3g` s
(3ChdgG (B:s
(3jbhd GdYHO GdabjQ Edi Gddg GdSejY GdeLjO , HOQ GdOjf eMeO Hf eMeO GdbhUhfi GdWHjH dWa Gddg Hg hGdeSdejf s
(3BNQgG (B:s
(3hJHjf Gdbhd GdUQjM ef GdHGWd GdeMGd ,hGdMeO ddg GdPi LYd WYf GdMGSOjf gPg GdebGdI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B260s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B179 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1782s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs